Ubiquitin-Specific Protease 25 Aggravates Acute Pancreatitis and Acute Pancreatitis-Related Multiple Organ Injury by Destroying Tight Junctions Through Activation of The STAT3 Pathway - Liu, Zhengru; Qi, Mingming; Tian, Shan; Yang, Qian; Liu, Jian; Wang, Siwei; Ji, Mengyao; Yu, Rong; Zeng, Suqi; Li, Jinting; Wei, Yuping; Dong, Weiguo (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitin-specific protease 25 (USP25) plays an important role in inflammation and immunity. However, the role of USP25 in acute pancreatitis (AP) is still unclear. To evaluate the role of USP25 in AP, we conducted research on clinical AP patients, USP25wild-type(WT)/USP25 knockout (USP25-/-) mice, and pancreatic acinar cells. Our results showed that serum USP25 concentration was higher in AP patients than in healthy controls and was positively correlated with disease severity. AP patients’ serum USP25 levels after treatment were significantly lower than that at the onset of AP. Moreover, USP25 expression was upregulated in cerulein-induced AP in mice, while USP25 deficiency attenuates AP and AP-related multiple organ injury. In vivo and in vitro studies showed that USP25 exacerbates AP by promoting the release of pro-inflammatory factors and destroying tight junctions of the pancreas. We showed that USP25 aggravates AP and AP-related multiple organ injury by activating the signal transducer and activator of transcription 3 (STAT3) pathway. Targeting the action of USP25 may present a potential therapeutic option for treating AP.